The Portrayal of Married Woman’s Life in Zemindar’s Wife by Qaisra Shahraz - Miftahur Roifah (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
Marriage is a social institution that adopts a patriarchal ideology to regulate the relationship between husband and wife. As a result, conflicts based on gender inequality can arise as patriarchal ideologies in marriage reinforce the dominance of men over women. A married woman’s life is often portrayed in feminist literature, such as in the short story of Qaisra Shahraz, Zemindar’s wife. This study analyzes the married life of Noor by applying the theory of Simone De Beauvoir in her book, The Second Sex. Besides, the study uses a qualitative approach with a close reading method. The results show that the short story Zemindar's Wife depicts the unequal gender relationship between husbands and wives in marriage. This gender imbalance leads to inequality, with women being dominated and subordinated by their husbands.